Pembuatan Bioetanol Dari Limbah Padat Sagu Menggunakan Enzim Selulase Dan Yeast Saccharomyces Cerevisiae Dengan Proses Simultaneous Sacharificatian and Fermentation (SSF) - Muria, Sri Rezeki; Nuryanti, Lidya; Chairul, Chairul (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2014)
Bioethanol is one of alternative energy that more friendly to environment because has an ability to reduce carbon dioxide emissions.  Biothehanol produced from fermentation process of glucose that comes from carbohydrate materials with the help of microorganism. The purposes of this research are to get the best operation condition that influenced by particle size and source of the nutrients to produce high level of biothanol and find the best time to do fermentation process. There are four step in this research, they are : preparation of material, equipment and nutrients sterilization, the making of inoculums and finally is scarification simultaneous fermentation process (SSF). Variations of particle size are 20-40 mesh and 60-80 mesh. Variations of nutrients source are come from urea and yeast extract. Fermentation process is done at pH 5 and room temperature. The highest level of biothanol produced by material with particle size  60-80 mesh and nutrients from urea. The best time for fermentation process is during 72 hours.  Key Words: Bioetanol, Cellulase enzym, Fermentation, solid waste of sago, Saccharomyces cerevisiae.